Network analysis of the EU insurance sector - Ivan Alves; Jeroen Brinkhoff; Stanislav Georgiev; Jean-Cyprien Héam; Iulia Moldovan; Carlo Marco Di Scotto (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2015)
This paper contains an analysis of the network of the 29 largest European insurance groups and their financial counterparties. Insurance companies have direct exposures to other insurers, banks and other financial institutions through the holdings of debt, equity and other financial instruments. These exposures can cause direct contagion and thereby the spread of systemic risks. This analysis focuses on direct linkages between EU insurers and banks. Sectoral data show that at least 20% of insurers' assets are investments in banks. As a result insurers are an important source of funding for banks. This paper adds to the expanding research on financial market networks and on systemic risks in the insurance sector.
Keywords: L14; G18; 330; network; insurance companies; systemic risk; contagion